The Impact of E-commerce on Consumer Behavior: An Empirical Study on Gen Z at STIE Cendekia Bojonegoro - Lailatul Fajriah; Khafid Nasrullah; Devinta Bintang Safitri; Eva Yogi Noor Laela (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The development of e-commerce has significantly transformed consumer behavior, particularly among Generation Z. This study examines the impact of e-commerce on the consumptive behavior of Gen Z students at STIE Cendekia Bojonegoro, Indonesia. E-commerce platforms offer easy access, a wide range of products, and various promotional features that influence consumer purchasing decisions. Using a quantitative approach with a survey design, this study investigates how promotions, social media, and other factors impact Gen Z's purchasing behaviors. The results reveal that social media has a more substantial influence on consumptive behavior than traditional promotional strategies, which were found to be less significant. This highlights the importance of social media in shaping the shopping habits of Gen Z. The findings contribute to a better understanding of e-commerce's role in influencing consumer behavior and offer recommendations for businesses and educational institutions to address the challenges associated with impulsive purchasing and financial management among students.